Good Governance in International Relations: Integrity Management and Locality in Nasrafa Painting Fabric - Susiatiningsih, Rr. Hermini Susiatiningsih; Faizal Alfian, Muhammad (JURNAL ILMU SOSIAL, 2023)
In the era of globalization, product internationalization is crucial for a company to reach the global market. The success of local businesses in reaching international markets needs to be supported by the involvement and collaboration of various actors. This research offers a unique insight into painted fabrics, an innovation of batik cloth as an original identity and cultural heritage of Solo (Central Java), which is a relatively new commodity that potentially penetrates international market. This study aims to examine and analyze the efforts of Nasrafais painting in Jebres Solo to penetrate the global market by exercising good governance and fostering collaborative relationships among various actors in multitrack diplomacy.  As one of the producers of painting fabric, Nasrafa has implemented local values and, as a result, earns prestigious national awards and grows foreign buyers. This research used the qualitative method, collecting primary data through interviews and discussing the collaborative effort between government, local business, and society in international relations, especially in the application of Good Governance. The results showed that the success of the export business was driven by massive, structured support from the government, corporations, and local citizens. An optimal, collaborative system can help establish the right conditions for industries to build domestic and international cooperation. This system is reflected in the production of Nasrafa painting fabric, indicating that the implementation of good governance can support multi-track diplomacy to accelerate the development and cooperation among actors in developing countries.